PELATIHAN PENULISAN DAN PEMBUATAN BAHAN AJAR RESPONDEN GENDER BAGI GURU SEKOLAH MENENGAH PERTAMA - Pairulsyah, Pairulsyah; Susetyo, Susetyo; Syani, Abdul; Suwarno, Suwarno (Prosiding Pengabdian FISIP Unila, 2012)
This training aims to increase participants understanding of the concept and scope of gender, gender policy in education, gender issues in schools, identify the gender gap in schools, identifying and formulating gender responsive teaching materials. The methods used are lectures, discussion, group work, discussions, and presentations. Training results indicate that, first, there was a significant improvement of the understanding of gender mainstreaming in education. Second, an increase in the skills on how to identify gender issues, redefined gender responsive education policy, and create regional action programs or activities on gender-responsive education. Third, there is increased awareness and commitment of the participants on the importance of implementing gender mainstreaming gender-responsive education of each school . Keywords: Teaching materials, Gender